Genetic Polymorphisms in 665bp Fragment of Exon 10 in Aryl Hydrocarbon Receptor - Nadhim MH (Journal of Global Pharma Technology, 2018)
A  cross sectional biochemical and molecular genetics study was achieved from December 2016 to September 2017, enrolled seventy patients (36 males, and 34 females) with somatotrophic pituitary adenoma continuously attended to the National diabetic center in Baghdad. Their ages were between 20 to 70 years. This research aimed to observe the frequency in 665bp fragment of exonic 10 of aryl hydrocarbon receptor (AHR) genes mutations. Polymerase chain reaction (PCR) was used for the detection ofAHRmutations as a cause of acromegaly, by using specific primers for amplification of exon 10 ofAHRgene on chromosome no.7. Sequencing was applied forPCRproducts ofAHRgene, ten different alterations inAHRgene were diagnosed .Four mutations inAHRwere recognized in 20/70 (29%) patients which their codons A474T with substitution adenine by thymine (A/T), 176 and 180 with substitution thymine by adenine (T/A), and codon 411 with substitution of (C/T) for 665bp.We concluded that ten novelties SNP were detected in Iraqi acromegalic cases. Genetic variants potentially inducing functional abnormalities of the aryl hydrocarbon receptor (AHR) pathway are associated with a more severe acromegaly, increased pituitary tumor size, and somatostatin analog resistance in patients living in HR areas.